"Pamali" Educational Values in Sundanese Society for Early Childhood - Ina Farida Arif (Early Childhood Education & Parenting, 2024)
The existence of pamali in Sundanese society today is often only seen as a myth as a way for parents to frighten their children, even though behind it lies various educational values related to cause and effect. Several studies related to pamali focus more on children aged over 6 years, while the educational values of pamali in Sundanese society for early childhood are still relatively rare. Through this literature review, the researcher then tries to identify pamali educational values that are still developing in Sundanese society today with educational values and character values that have been formulated by the Curriculum Center of the Research and Development Agency of the Ministry of National Education. It is hoped that with this research, pamali can be an alternative to local wisdom-based education that can be implemented in early childhood.